Problem Posing Learning Model For Developing Students’ Natural Disaster Responsiveness Characeters in Indonesia (A Case Study in State Senior High Schools in Kerinci) - Darysyani, Dhea (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This study aims to develop students’ responsiveness character on natural disaster through the implemtation of Problem Posing Learning Model in SMA Negeri Kerinci. The research was Mixed Method research. The data was obtained thorugh observation, interview and documentation. Furthermore, the data was analysed by calculating its percentage and scores followed data reduction, interpretation and research conclusion. The results showed that the implementation of Problem Posing Learning Model in developing the character of natural disaster responsiveness has been well conductedStudents’ responsiveness character on natural disaster, For example: throwing garbage in its place, planting trees that are beneficial for life requires: knowledge, understanding, appreciation, confidence, awareness and practice, awareness to reduce 5 disaster risks, awareness in investing to reduce disaster risk, eg reforestation to prevent flooding. One of the disaster mitigation efforts in developing natural disaster responsiveness characters can be done by students’ response attitude. The result of Geography learning in SMA Negeri 6 Kerinci was 83.621, higher that SMA Negeri 3 Kerinci based on the hypothesis testing . Obtained data showed a significant differences between the school that implemented Problem Posing Learning Model in Geography classroom the school that did not implement the learning model. Finally,it was ound that the implementation of Problem Posing Learning Model in geography learning could improve students’ respnsiveness character on natural disaster in Indonesia